Digital Transformation in SMEs: Enablers, Interconnections, and a Framework for Sustainable Competitive Advantage - Eyup Kahveci (Administrative Sciences)
This study identifies critical success factors contributing to the digital transformation of SMEs. Despite their crucial role in the economy, limited research explores how they navigate digitalization challenges. This study addresses this gap by proposing the DASAT framework with four cyclically interrelated elements: Digital Awareness, Digital Strategy and Roadmap, Digital Adoption and Implementation, and Digital Transformation Continuous Improvement. Using a Total Interpretive Structural Modeling (TISM) approach, we construct a hierarchical model analyzing the interconnections among key factors. The findings align with the dynamic capability framework and digital transformation theory, emphasizing digital literacy, digital inclusion, and organizational flexibility for SMEs’ successful digital transformation. This study contributes theoretically by extending the digital transformation literature with a structured capability-building framework. It provides a practical roadmap for SMEs to strengthen their competitive advantage in an increasingly digital business environment.